Correction: Elucidating time-dependent changes in the urinary metabolome of renal transplant patients by a combined 1H NMR and GC-MS approach. Issue 2 (19th January 2017) - Muhrez, Kienana; Nadal-Desbarats, Lydie; Halimi, Jean-Michel; Dieme, Binta; Büchler, Matthias; Emond, Patrick; Blasco, Hélène; Le Guellec, Chantal
Abstract : Correction for 'Elucidating time-dependent changes in the urinary metabolome of renal transplant patients by a combined 1 H NMR and GC-MS approach' by Kienana Muhrez et al., Mol. BioSyst., 2015, 11, 2493–2510.